(untitled) (Journal of Science Foundation, 2013)
Fractions studies were done to know how the zinc applied to different soils was distributed in to various fractions when the soils incubated under aerobic and anaerobic condition. The added zinc provided significant increase in exchangeable Zn both under aerobic and anaerobic conditions although anaerobic condition gave lower results than aerobic condition. The higher results were obtained at early stage of incubation and it gradually reduced as the incubation period proceeded to 90 days. These results showed all most similar trends for all the soils under study. In general, added zinc showed significantly higher results to the different fractions of soil Zn both under anaerobic and aerobic incubation with very few exceptions. The highest amount of added Zn (12 kg/ha) always produced greater results than the lower doses. Only exchangeable Zn was found higher in the 1st measurement at 15 DAI then gradually decreased but in other cases, gradual increase in zinc fractions was seen as the incubation study proceed to longer duration provided with very few exceptions. In many cases, the exchangeable-Zn found higher only at 15 DAI but sharply reduced at 30 DAI. In general, the Gray Terrace Soil produced the highest results followed by Non Calcareous Gray Floodplain and the lowest results were observed in Dark Grey Floodplain & Brown Floodplain Soil. DOI: http://dx.doi.org/10.3329/jsf.v9i1-2.14643 J. Sci. Foundation, 9(1&2): 9-15, June-December 2011